Reducing the incidence of Fall Army Worm (FAW) in irrigated maize (Zea mays L.) through intercropping systems - Sivamurugan, A P; Suganthi, A; Pazhanivelan, S; Manivannan, V; Raju, M; Bharathi, C (Plant Science Today, 2025)
Pest management strategies involving intercropping systems are being developed in different research stations. However, findings on location specific management are very limited. In order to address these problems and enhance maize productivity by identifying location specific strategies, field experiments were conducted at the Department of Millets, Tamil Nadu Agricultural University, Coimbatore during kharif, 2020 and rabi, 2020-21 to reduce the incidence of FAW in irrigated maize through different intercropping systems in sandy clay loam soil. The experiments consisted of 5 treatments viz., T1- Maize + Tephrosia, T2- Maize + Fenugreek, T3- Maize + Coriander, T4- Maize + Marigold and T5- Maize alone and these were laid out in a Randomized Complete Block Design (RCBD) with 3 replications. On the border of experimental field, a row of Bajra Napier Hybrid grass was planted to study the influence on FAW. The results of experiments revealed that the T4- Maize + Marigold treatment was superior in reducing the incidence of FAW in irrigated maize among the different intercropping systems owing to the occurrence of natural enemies and repelling nature of marigold which recorded higher maize equivalent yield of 6089 kg ha-1 with a B:C ratio of 1.84. This system of intercropping should be adopted by the farming community to reduce the incidence of FAW in maize as it is an eco friendly approach, which sustains the productivity of maize.